Microenzyme-linked immunosorbent assay for the detection of specific IgM antibodies in human syphilis. Issue 3 (June 1983) - Lindenschmidt, E G; Laufs, R; Müller, F
Abstract : An enzyme-linked immunosorbent assay (ELISA) using a highly purified soluble antigen prepared from pathogenic Treponema pallidum (Nichols) was carried out to detect specific IgM antibodies in syphilis. Serum specimens from 365 patients with untreated or treated syphilis were tested by the ELISA and by the 19S(IgM) fluorescent treponemal antibody-absorbed test. In the ELISA sera were preabsorbed with aggregated human IgG to eliminate any rheumatoid factor present. Sera from 331 healthy blood donors served as controls. The results of both tests correlated well. The specificity and sensitivity of the treponemal ELISA were both greater than 97%. The assay was easy to perform and may be automated.